1998
DOI: 10.1172/jci2545
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin-4 in fast-twitch fibers of mammalian skeletal muscle.

Abstract: In this study we analyzed the expression of aquaporin-4 (AQP4) in mammalian skeletal muscle. Immunohistochemical experiments revealed that affinity-purified AQP4 antibodies stained selectively the sarcolemma of fast-twitch fibers. By immunogold electron microscopy, little or no intracellular labeling was detected. Western blot analysis showed the presence of two immunopositive bands with apparent molecular masses of 30 and 32 kD specifically present in membrane fraction of a fast-twitch rat skeletal muscle (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 37 publications
7
158
0
3
Order By: Relevance
“…Our observation that AQP-1 is expressed on the cell membranes of myoepithelial cells that surround the acini of salivary glands has intriguing parallels in the observations of AQP expression in the cell membranes of other excitable contractile cells, including those of smooth muscle cells (Gannon et al, 2000;Shanahan et al, 1999), cardiac muscle cells (Page et al, 1998), and the sarcolemma of fast-twitch skeletal muscle fiber (Frigeri et al, 1998). AQP-1 has been shown to mediate accelerated smooth muscle volume changes in response to altered external osmolarity (Shanahan et al, 1999), suggesting that variation in cell volume mediated by AQP-1 may contribute to contraction and/or variation in tone of vascular smooth muscle (Shanahan et al, 1999).…”
Section: Role Of Aqp-1 In Myoepithelial Cell Functionsupporting
confidence: 66%
“…Our observation that AQP-1 is expressed on the cell membranes of myoepithelial cells that surround the acini of salivary glands has intriguing parallels in the observations of AQP expression in the cell membranes of other excitable contractile cells, including those of smooth muscle cells (Gannon et al, 2000;Shanahan et al, 1999), cardiac muscle cells (Page et al, 1998), and the sarcolemma of fast-twitch skeletal muscle fiber (Frigeri et al, 1998). AQP-1 has been shown to mediate accelerated smooth muscle volume changes in response to altered external osmolarity (Shanahan et al, 1999), suggesting that variation in cell volume mediated by AQP-1 may contribute to contraction and/or variation in tone of vascular smooth muscle (Shanahan et al, 1999).…”
Section: Role Of Aqp-1 In Myoepithelial Cell Functionsupporting
confidence: 66%
“…At the beginning of this study we predicted the presence of AQP4 in the blood-nerve barrier as seen in the blood-brain barrier. However, AQP4 was not detected in the peripheral nervous system, although AQP4 in skeletal muscle fibers [3] was properly labeled (data not shown). We found that AQP1 is present in the perineurium and some blood vessels inside the nerve fiber bundle.…”
Section: Discussionmentioning
confidence: 89%
“…F0205, Denmark) diluted 1:50 in PBS for 60 min at room temperature. For the judgment of myofiber type [19], serial sections of HE or oil red O stained muscle samples and the immunostained muscle samples with anti-AQP7 or AQP9 antibody from obese DIO or control chow-fed mice were also immunostained with the affinity purified rabbit anti-AQP4 antibody at the IgG concentration of 5 µg/ml [18]. The immunostained muscles were examined using Nikon H 550L fluorescent microscope.…”
Section: Histopathological and Immunohistochemical Studiesmentioning
confidence: 99%